Akceptacja choroby kobiet leczących się z powodu osteoporozy = Acceptance of diseases of women treated for osteoporosis - Pawlikowska-Łagód, Katarzyna; Janiszewska, Mariola; Firlej, Ewelina; Dąbska, Olga; Sak, Jarosław (Journal of Education, Health and Sport, 2016)
Pawlikowska-Łagód Katarzyna, Janiszewska Mariola, Firlej Ewelina, Dąbska Olga, Sak Jarosław. Akceptacja choroby kobiet leczących się z powodu osteoporozy = Acceptance of diseases of women treated for osteoporosis. Journal of Education, Health and Sport. 2016;6(5):139-148. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.51372 http://ojs.ukw.edu.pl/index.php/johs/article/view/3515 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.04.2016. Revised 29.04.2016. Accepted: 11.05.2016. Akceptacja choroby kobiet leczących się z powodu osteoporozy Acceptance of diseases of women treated for osteoporosis Pawlikowska-Łagód Katarzyna1, Janiszewska Mariola2, Firlej Ewelina2, Dąbska Olga3, Sak Jarosław1 1Zakład Etyki i Filozofii Człowieka, Uniwersytet Medyczny w Lublinie 2Katedra Zdrowia Publicznego, Uniwersytet Medyczny w Lublinie 3Zakład Patologii i Rehabilitacji Mowy, Uniwersytet Medyczny w Lublinie mgr Pawlikowska-Łagód Katarzyna, dr n. o zdr. Janiszewska Mariola, mgr Firlej Ewelina, Dąbska Olga, dr hab. n med. Sak Jarosław Abstrakt Wprowadzenie: Współczesna medycyna oraz psychologia coraz więcej czasu poświęcają problemom związanym z osteoporozą oraz przystosowaniu się do niej. Przystosowanie się i akceptacja osteoporozy to skomplikowany proces, na, który wpływają obciążenia chorobowe, uwarunkowania zewnętrzne oraz właściwości jednostki. Akceptacja choroby dla wielu pacjentek jest problemem, z którym zmagają się przez cały okres jej trwania, zmuszając je do akceptacji niedomagań przez nią narzuconych choroby. Pojawienie się choroby ma duże znaczenie, dla jakości życia kobiet. Przede wszystkim zmuszając je do akceptacji niedomagań narzuconych przez chorobę. Cel pracy: Celem pracy było zbadanie stopnia akceptacji choroby kobiet chorujących na osteoporozę. Materiał i metody: W badaniu uczestniczyło 137 pacjentek leczących się z powodu osteoporozy. Grupę badaną stanowiły kobiety od 38-go do 91-g roku życia. Badania przeprowadzono od lutego do kwietnia 2015 roku. W pracy zastosowano kwestionariusz ankiety własnego autorstwa oraz Skalę Akceptacji Choroby (AIS) autorstwa B. J. Felton, T. A. Revenson i G. A. Hinrichsen w adaptacji Z Jurczyńskiego. Wyniki: Kobiety chorujące na osteoporozę wykazują się średnim stopniem akceptacji choroby. Wiek zdiagnozowania choroby oraz wykształcenie różnicuje istotnie badane ze względu na stopień akceptacji choroby oraz problemów narzuconych przez chorobę. Wnioski: Rosnąca liczba osób chorych z powodu osteoporozy stawia przed specjalistami służby zdrowia ogromne wyzwanie. Wdrożenie skutecznych programów profilaktycznych oraz oddziaływanie na zwiększenie świadomości chorujących byłoby pomocne w zapobieganiu chorobie, ewentualnie jej akceptacji w sytuacji wystąpienia. Abstract Introduction: Modern medicine and psychology more and spend more time problems with osteoporosis and adapt to it. Adaptation and acceptance of osteoporosis is a complex process, for which affect disease burden, external conditions and the characteristics of the individual. Acceptance of the disease for many patients is a problem faced by the whole period of its duration, forcing them to accept the shortcomings imposed by her illness. The emergence of the disease is important for the quality of life of women. First of all, forcing them to accept the shortcomings imposed by the disease. The aim of the study was to examine the degree of acceptance of the disease women suffering from osteoporosis. Material and Methods: The study included 137 patients treated for osteoporosis. The study group were women from 38 th to 91th years. The study was conducted from February to April 2015. The study used a questionnaire survey of his own authorship and Acceptance of Illness Scale (AIS) by B. J. Felton, Revenson T. A. and G. A. Hinrichsen adaptation With Jurczyński. Results: Women suffering from osteoporosis have an average degree of acceptance of the disease. Age diagnose the disease and education differentiates significantly tested due to the degree of acceptance of the disease and the problems imposed by the disease. Conclusions: The increasing number of patients suffering from osteoporosis poses to health care professionals a huge challenge. The implementation of effective prevention programs and impact on increasing awareness of suffering would be helpful in the prevention of disease, or to accept it in a situation occur. Słowa kluczowe: akceptacja choroby, osteoporoza, kobieta. Keywords: acceptance of illness, osteoporosis, women.